Finland : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
This 2005 Article IV Consultation highlights that Finland's economic performance in recent years continued to be favorable. Growth has outpaced that in the euro area and is expected to pick up to more than 3 percent in 2006. The external current account has remained comfortably in surplus, and inflation has remained below the euro area average. The authorities are taking some steps to address the long-term fiscal pressures. Proposals are also being debated to reform the financing of local governments and restructure their activities to raise efficiency in the provision of public services.